Daya Dukung dan Eisiensi Produksi Sapi Madura dengan Pemanfaatan Limbah Kacang Kedalai - Rab, S. A.; Priyanto, R.; Fuah, A. M.; Wiryawan, I. K. G. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
The aim of this study was to evaluate productivity of beef cattle through the utilization soybean by-product.Twelve Madura cattle with and average initial liveweight of 175.64 ± 16.41 kg and aged between I1-I2 (18-30 months) were used in this study fattened for three monthsgiven differentfeeds level, ie. P0 (100% native grass), P1(40% roughage + 60% concentrate), P2(15% of soybean pod+ 85% concentrate), and P3(30% soybean pod + 70% concentrate). Observed parameters included production of soybean waste per hektar, carry capacity of cattle based of soybean waste, income over feed cost (IOFC), andRC ratio.The results showed that the production of soybean pods and tofu waste was 1.75 ton/ha, and 0.44 ton/ha. This results indicated that carry capasity of soybean wastes for cattle production was of8,95 ST/ha/year, and 1,91 ST/ha/year respentively. Economy analisis based on income over feed cost and R/C ratio results showed that use of soybean waste was to replaces forage quite potensial for farmer, especially in the region to here soybean production is high.